(3eMGSf GdeLGdSs - (3CMeO Hf eMeO Hf ehSi GdUfgGLj GdCfOdSj GdeQj, CHh GdYHGS , GHf GdnYQja,J (B536 (3g` s
(3ChdgG (B:s
(3bGd GdCSJGP CMeO Hf eMeO GdUhai GdUfgGLi QMeg Gddg Ydjg (B: (3bO ESJNQJ Gddg JYGdi ai LeY aUhd ef eMGSf GdcdGe GdUGOQI Yf Cgd GdEdgGe s
(3BNQgG (B:s
(3hfSCdg Cf jLYdfG hEjGce eYTQ GdENhGf HeG YdefG Hg YGedjf hdhLgg eQjOjf hCf dGjLYdg hHGdkG YdjfG agPG BNQ eG CQOfG Cf fPcQg ai TQM cjajI Sdhc WQjb GdBNQI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B164s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1609s
Keywords: (3GdJUha hGdBOGH GdTQYjIs